A Cesium Rare‐Earth Silicate Cs3RESi6O15 (RE=Dy–Lu, Y, In): The Parent of an Unusual Structural Class Featuring a Remarkable 57 Å Unit Cell Axis. Issue 8 (1st February 2018) - Terry, Rylan; Vinton, Daniel; McMillen, Colin D.; Kolis, Joseph W.
Abstract: The structure of Cs3 RESi6 O15, where RE=Dy–Lu, Y, In, is unusual in that it contains octahedrally coordinated rare‐earth ions; their relative orientation dictates the structure, as they rotate about the c ‐axis supported by the cyclic Si6 O15 framework. The repeat unit of the rotation is eight units generating a very long (ca. 57 Å) unit cell axis. This unusual repeat unit is created by the structural flexibility of the hexasilicate ring, which is in turn affected by the size of the rare earth ion as well as the size of alkali ion residing within the silicate layers. Previous work showed for the smaller Sc 3+ ion, the rotation of the octahedra is not sufficient to achieve closure at an integral repeat unit and an incommensurate structure results. The products are prepared as large, high quality single crystals using a high‐temperature (650 °C) hydrothermal method with CsOH and F − mineralizers. The presence of fluoride is essential to the formation of the product. Abstract : A series of cesium rare‐earth silicates, Cs3 RE(Si6 O15 ) (RE=Dy–Lu, Y, In), has been synthesized and structurally characterized. The structure, containing a long c ‐axis of about 57 Å, provides a fully ordered baseline structural model to which other alkali–rare‐earth silicates exhibiting modulated or disordered structures can be related.